Pengembangan pembelajaran anak usia dini berbasis Teknologi Informasi dan Komunikasi - Rusmayadi Rusmayadi (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Information and Communication Technology (ICT)is a product of human intelligence, but Information andCommunication Technology (ICT) can also affect humanintelligence. Research on the influence of Information andCommunication Technology (ICT) on intelligencedevelopment has been carried out by experts. The results,among others, show that the correct use of Information andCommunication Technology (ICT) reciprocally affectsintelligence. When equipped with applications, Informationand Communication Technology (ICT) is able to fulfill humancuriosity. In addition, speed, accuracy, and updatedinformation can be obtained through a network system, so asto provide enrichment of the brain function of its users.Therefore, early childhood educators need to know,understand, design and develop Information andCommunication Technology (ICT) in developing earlychildhood learning.